Effect of doping elements on catalytic performance of CeO2-ZrO2 solid solutions - 李梅 柳召刚 胡艳宏 王觅堂 励杭泉 (Journal of rare earths, 2008)
CeZr, CeYZr, LaCeZr, LaCePrZr, LaCePrYZr, and LaCePr solid solutions were prepared via the coprecipitation method, and characterized by means of X-Ray Diffraction （XRD） and Brunauer-Emmett-Teller （BET） techniques. The oxygen storage capacity （OSC） of the solid solutions was evaluated by the pulse technique and the catalytic activity was assessed using a 4-channel catalysis device. It was seen that the solid solutions presented cubic structure. The specific surface area and thermal stability could be enhanced by doping Y into the solid solutions. Doping a small amount of La had a positive effect on the thermal durability while doping a large amount of La decreased the specific surface area and the thermal stability. LaCePrZr and LaCePrYZr solid solutions synthesized using Baotou rare earth mineral residue enriched with LaCePr after Nd extraction presented a certain higher value in specific surface area and thermal stability, thereby enabling to be used as economic catalysts for automobile exhaust purification. Coating Al2O3 or SiO2 layer on the surface of ceria-zirconia solid solutions increased the specific surface area and thermal resistance.